Rationale and design of the Children's Oncology Group (COG) study ALTE1621: a randomized, placebo-controlled trial to determine if low-dose carvedilol can prevent anthracycline-related left ventricular remodeling in childhood cancer survivors at high risk for developing heart failure. Issue 1 (December 2016) - Armenian, Saro; Hudson, Melissa; Chen, Ming; Colan, Steven; Lindenfeld, Lanie; Mills, George; Siyahian, Aida; Gelehrter, Sarah; Dang, Ha; Hein, Wendy; Green, Daniel; Robison, Leslie; et al.
Abstract Background Anthracyclines are widely used in the treatment of childhood cancer. One of the well-recognized side-effects of anthracycline therapy is dose-dependent cardiomyopathy that may progress to heart failure (HF) years after completion of cancer-directed therapy. This study will evaluate the efficacy of low-dose beta-blocker (carvedilol) for HF risk reduction in childhood cancer survivors at highest risk for HF. The proposed intervention has the potential to significantly reduce chronic cardiac injury via interruption of neurohormonal systems responsible for left ventricular (LV) remodeling, resulting in improved cardiac function and decreased risk of HF. The intervention is informed by previous studies demonstrating efficacy in pediatric and adult non-oncology populations, yet remains unstudied in the pediatric oncology population. Methods/Design The primary objective of the trial is to determine impact of the intervention on echocardiographic markers of cardiac remodeling and HF risk, including: LV wall thickness/ dimension ratio (LVWT/D; primary endpoint), as well as LV ejection fraction, volume, and blood biomarkers (natriuretic peptides, galectin-3) associated with HF risk. Secondary objectives are to establish safety and tolerability of the 2-year course of carvedilol using: 1) objective measures: hepatic and cardiovascular toxicity, treatment adherence, and 2) subjective measures: participant self-reported outcomes. Two hundred and fifty survivors of childhood cancer (diagnosed <21 years of age), and previously treated with high-dose (≥300 mg/m2 ) anthracyclines will be enrolled in a randomized, double-blind, placebo controlled trial. After baseline assessments, participants will be randomized in a 1:1 ratio to low-dose carvedilol (maximum dose: 12.5 mg/day) or placebo. Carvedilol or placebo is up-titrated (starting dose: 3.125 mg/day) according to tolerability. Discussion When completed, this study will provide much-needed information regarding a physiologically plausible pharmacological risk-reduction strategy for childhood cancer survivors at high risk for developing anthracycline-related HF. Trial registration ClinicalTrials.gov;NCT02717507